Ophiuroids (Echinodermata; Ophiuroidea) of biogenic habitats on the continental shelf of New Zealand - Mills, V. Sadie; O'hara, Timothy D. (Zootaxa, 2013)
The taxonomy of ophiuroids collected in 2009 and 2011, from biogenic habitats across the New Zealand continental shelf, is reviewed. Ophionereis novaezelandiae Mortensen, 1936, and its junior synonym Ophionereis terba Baker & Devaney, 1981from South-Eastern Australia, is now recognised as a distinct species, and has been removed from synonymy with Ophionereis fasciata Hutton, 1872. Ophiacantha abyssicola var. otagoensis Fell, 1958 is also recognised as a distinct spe-cies and has been removed from synonymy with Ophiacantha brachygnatha Clark H L, 1928. Amphiura eugeniae var. latisquama Mortensen, 1924 is raised to species rank and Amphioplus longirima Fell, 1952 treated as a synonym of A. latisquama. Ophiolycus farquhari McKnight, 2003 is transferred to the genus Ophiologimus. The diagnostic characters of several other species are reviewed and colour descriptions and images are included where available. The tropical species Ophiacantha longidens Lyman, 1878, Ophiotreta valenciennesi (Lyman, 1879) and Ophiobyrsa intorta (Koehler, 1922) are reported from New Zealand waters for the first time.